2014
DOI: 10.1007/s00429-014-0760-6
|View full text |Cite|
|
Sign up to set email alerts
|

A new window to understanding individual differences in reward sensitivity from attentional networks

Abstract: Revista:Brain Structure and Function, 2014 Abstract:Existing evidence suggests that the presence of reward cues modifies the activity in attentional networks; however, the nature of these influences remains poorly understood. Here, we performed independent component analysis (ICA) in two fMRI datasets corresponding to two incentive delay tasks, which compared the response to reward (money and erotic pictures) and neutral cues, and yielded activations in the ventral striatum using a General Linear Model approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 78 publications
2
10
0
1
Order By: Relevance
“…Existing evidence suggests that trait impulsivity is a risk factor for drug experimentation, problematic drug use and inability to abstain from drug use (De Wit ). It has also been shown that impulsivity‐related traits modulate the response of functional networks during reward processing (Costumero et al ). Thus, further studies should differentiate the specific effects of dispositional factors and cocaine abuse in FPN modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence suggests that trait impulsivity is a risk factor for drug experimentation, problematic drug use and inability to abstain from drug use (De Wit ). It has also been shown that impulsivity‐related traits modulate the response of functional networks during reward processing (Costumero et al ). Thus, further studies should differentiate the specific effects of dispositional factors and cocaine abuse in FPN modulation.…”
Section: Discussionmentioning
confidence: 99%
“…SICA may have a better specificity and sensitivity than GLM-BA and show novel feature of brain functional organization not revealed by GLM-BA such as extensive overlaps of FNs with opposite timecourses of task-related activities (Beldzik et al, 2013; Costumero et al, 2014; Domagalik et al, 2012; Xu et al, 2014b; Xu et al, 2015), due to its unique capacity of separating intermixed signals. In one of our recent studies, a GLM-BA revealed task-related increases, decreases, and no-changes in BOLD signal in separate brain regions.…”
Section: An Approach For Addressing These Brain Propertiesmentioning
confidence: 99%
“…The ICs of interest are usually selected as follows [4042]:ICs with a stability index <0.9 in ICASSO must be removed; in the present study none of the estimated ICs were eliminated using this criterion.ICs are spatially sorted according to the templates of gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF) included in SPM8; those ICs whose values of R 2 > 0.02 for WM, R 2 > 0.05 for CSF, and those whose value of R 2 for GM is lesser than that obtained for WM and/or CSF are also discarded. In this study, after performing this step 6 ICs with values of R 2 > 0.02 for WM were discarded; no ICs with R 2 > 0.05 for CSF were found; and 8 ICs with R 2 value for GM less than that obtained for the other tissues were discarded.…”
Section: Methodsmentioning
confidence: 99%